Orbital Blood Flow and Pseudoexfoliation Syndrome - A Narrative Review - Anujeet Paul; Aishwarya Naik; Prasanna V. Ramesh; Tamanna Ghosh (TNOA Journal of Ophthalmic Science and Research)
The narrative review titled ‘Orbital Blood Flow and Pseudoexfoliation Syndrome’ provides a comprehensive exploration of the intricate interplay between pseudoexfoliation (PEX) syndrome and orbital blood flow, offering insights into its clinical ramifications. Commencing with an overview of the historical context and prevalence of PEX, the review traverses various dimensions, including gender and age considerations, mortality/morbidity rates, and the underlying pathophysiology. It delves into the composition of PEX material and delineates the differential gene expression associated with the syndrome. Central to the discourse is the impact of PEX on orbital vasculature, elucidating its correlation with ocular ischemia and alterations in protein levels within the aqueous humour. Techniques for clinical evaluation, notably colour Doppler imaging, emerge as indispensable tools for assessing blood flow in patients with PEX.The article emphasises the significance of vascular dysfunction in PEX, highlighting the findings of decreased blood flow velocities and elevated resistive indices in affected individuals.The review underscores the imperative of comprehending the vascular implications of PEX to optimise diagnostic and management approaches, with far reaching implications for minimising operative complications and enhancing patient outcomes.